2013
DOI: 10.1111/1471-0528.12464
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal and perinatal consequences of antepartum haemorrhage of unknown origin

Abstract: Objective To explore the risk of adverse maternal and perinatal outcomes in women with antepartum bleeding of unknown origin (ABUO).Design Cohort study based on data extracted from the Aberdeen Maternity and Neonatal Databank. Exposure was antepartum haemorrhage occurring after the first trimester not attributable to placenta praevia or placental abruption.Setting Aberdeen Maternity Hospital, Aberdeen, Scotland, UK.Population All primigravidae delivering between 1976 and 2010.Methods Data were analysed using u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 20 publications
3
39
0
2
Order By: Relevance
“…However, the authours could not comment conclusively from their dataset on whether this was due to spontaneous preterm labour or induction of labour before term. 1 Our retrospective comparative cohort study using individual case records in a National Health Service hospital in the UK suggested that in cases of unexplained APH, preterm delivery (<37 weeks) is attributed to spontaneous preterm labour (15.4% in unexplained APH versus 5.9% in controls; P < 0.001). 4 We were able to address this issue only because individual case notes were reviewed in this retrospective cohort study, where maternal and perinatal outcomes of 287 women with unexplained APH were compared with the outcomes of 424 controls macthed for age, parity and day of delivery.…”
Section: Sirmentioning
confidence: 86%
See 1 more Smart Citation
“…However, the authours could not comment conclusively from their dataset on whether this was due to spontaneous preterm labour or induction of labour before term. 1 Our retrospective comparative cohort study using individual case records in a National Health Service hospital in the UK suggested that in cases of unexplained APH, preterm delivery (<37 weeks) is attributed to spontaneous preterm labour (15.4% in unexplained APH versus 5.9% in controls; P < 0.001). 4 We were able to address this issue only because individual case notes were reviewed in this retrospective cohort study, where maternal and perinatal outcomes of 287 women with unexplained APH were compared with the outcomes of 424 controls macthed for age, parity and day of delivery.…”
Section: Sirmentioning
confidence: 86%
“…The interesting article by Bhandari et al 1 has inspired us to put forward a few comments/queries regarding their study design and its interpretation. This retrospective cohort study included routinely coded data from a databank.…”
Section: Sirmentioning
confidence: 99%
“…This is not a surprising finding, as antepartum hemorrhage is a widely known risk factor for stillbirth or perinatal death. [11][12][13] Therefore its association with nuchal cord might increase this risk.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Drs Jana, Barik and Arora for their interest in our paper 1 . The authors have raised some valid issues which we will try to clarify.…”
Section: Sirmentioning
confidence: 99%